The disclosure of politics : struggles over the semantics of secularization - Lara, María Pía (New directions in critical theory., 2013)
María Pía Lara explores the ambiguity of secularization and the theoretical potential of a structural break between politics and religion. For Lara, secularization means the translation of religious semantics into politics; a transformation of religious notions into political ideas; and the reoccupation of a space left void by changing political actors, one that gives rise to new conceptions of political interaction. Conceptual innovation redefines politics as a horizontal relationship between governments and the governed, better enabling societies (and political actors) to articulate mea.